Bank Disclosure Practices in Bangladesh: Exploring the Impact of Corporate Attributes - Neogy, Taposh Kumar (American Journal of Trade and Policy, 2023)
Disclosure is necessary so that interested parties can make wise decisions. The study aims to establish the level of disclosure and whether different corporate attributes influence it. Each sample bank’s disclosure score was calculated using the unweighted disclosure index. Throughout five years, spanning 2016 to 2020, the necessary data were collected from sample banks’ annual reports, and several statistical tools were employed to illustrate the study’s conclusions. The study’s findings report that the average level of disclosure is satisfactory. The ANOVA test was used to establish whether there was a significant difference in the disclosure levels, and the results show a substantial difference in this case. Multiple regression analysis was performed to investigate the effect of various corporate attributes on disclosure levels. The study’s consequences showed that although these variables had significant values higher than 0.05, ROE, EPS, CAR, and log number of employees had no significant influence on disclosure levels. However, at the 0.05 significance level, log total assets demonstrate 0.055 significant levels, indicating that LTA considerably influences disclosure levels.